Non-isothermal crystallization of biodegradable polymer (MaterBi)/polyolefin (PP)/hemp fibres ternary composites - Pérez, Claudio Javier (2015)
The non-isothermal crystallization of biodegradable thermoplastic matrix (Mater-Bi, MB) and traditional thermoplastic (polypropylene, PP) blends was studied using differential scanning calorimetry (DSC). Hemp fibres were used as filler, and maleic anhydride functionalized polypropylene (PP*) was employed as compatibilizer. MB forms immiscible blends with PP. Both, molten MB act as nucleating agent enhancing the crystallization rate of PP and the solidified PP act as nucleating agent to enhance the crystallization of MB. The values of half-time of crystallization (t1/2) and the parameter Zc, from Avrami’s method which characterize the kinetics of non-isothermal crystallization, showed that the crystallization rate, at the same cooling rate, decreased with the fibres and increased with the PP*; showing the retarding and accelerating effects, respectively. Some models, such as the Liu-Mo and Avrami, were found to provide a fairly satisfactory description of the crystallization kinetics of the studied blends. These results are further supported by the effective activation energy calculations by iso-conversional method of Friedman.